Hidrosefalus Dalam Biologi Molekuler - Ni Wayan Suarniti; Ni Komang Yuni Rahyani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2020)
ABSTRACTHydrocephalus is a health problem that affects the nervous system (neurobehavior). Hydrocephalus treatment is included in the category of "live saving and live sustaining" which means that this disease requires early diagnosis followed by immediate surgery. Delay will cause disability and death so that the principle of hydrocephalus treatment must be fulfilled. Hydrocephalus is a pathological condition of the brain that results in increased cerebrospinal fluid and an increased intracranial pressure (ICP) so that there is a widening of the room where the discharge is issued. The incidence of hydrocephalus is estimated to be close to 1: 1000. whereas the incidence of congenital hydrocephalus varies for each different population. Recent research shows hydrocephalus can be triggered by abnormal levels of lysophosphatidic acid (LPA), blood lipids that enter the brain in high concentrations during bleeding events, with a profound effect on developing brain cells. Likewise with the diagnostic examination of hydrocephalus, cerebrospinal fluid (CSF) biomarkers have now been found that can be used as markers of changes in the brain environment related to the state of the brain itself. With this research in the field of molecular biology, even for therapy even though LPA1-blocking is being developed, a drug that is currently being developed for its use in the management of hydrocephalus. Given the complications that can be caused by hydrocephalus, more research is needed. For medical personnel and paramedics, in order to be able to further enhance their competence in order to provide care to hydrocephalus patients as well as possible. Keyword:  biomarkers, cerebrospinal fluid, hydrocephalus